ANALYSIS OF THE IMPLEMENTATION OF THE CASH ON DELIVERY (COD) SYSTEM AND ITS ROLE IN SUPPORTING ONLINE BUSINESS DEVELOPMENT AT FLAMBOYAN SMES, GORONTALO CITY - Hartin Hasdin; Djamila Podungge; Nuzmerini Rauf (LP2M Universitas Bina Mandiri Gorontalo, 2026)
This study aims to analyze the application of the Cash on Delivery (COD) payment system in increasing online business sales and to identify the strategies employed by Flamboyan SME in Gorontalo City to mitigate operational risks associated with COD transactions. The research adopts a qualitative descriptive approach using in-depth interviews, field observations, and documentation techniques. Informants consisted of the business owner and operational staff directly involved in managing online sales activities. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that the implementation of the COD system has significantly expanded market reach and increased sales by attracting consumers who prefer secure payment methods and have limited trust in digital transactions. Flamboyan SME successfully mitigates common COD-related risks through personalized communication via WhatsApp, which strengthens customer trust and loyalty, as well as through strict product quality control and premium packaging differentiation. These strategies minimize product returns, reduce customer complaints, and encourage repeat purchases. Despite challenges related to limited third-party logistics availability during late-night hours, the enterprise maintains customer satisfaction through responsive communication and consistent service quality. The study concludes that the integration of COD, digital trust-building, and product differentiation contributes positively to online sales growth and business sustainability.